The Impact of Generative AI on B2B Marketing Processes: Evidence from Industrial Firms - Vesterinen, Mikko; Mero, Joel; Skippari, Mika; Karjaluoto, Heikki (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Generative artificial intelligence (GenAI) is transforming marketing, yet its implications for B2B marketing processes and skills remain insufficiently understood, particularly in industrial contexts where AI adoption has lagged. This study examines how GenAI is used in industrial marketing, its impact on B2B marketing processes, and what skills marketers need. Drawing from 43 semi-structured interviews with AI and marketing leaders from multinational industrial firms and technology providers, we map GenAI applications across marketing information management, planning, and implementation, and categorize them by input type and degree of human augmentation. The findings reveal an uneven impact: GenAI affects implementation most, with increasing automation and customization, whereas its use for information management and planning remains largely unsystematic. As automation increases, marketers’ roles shift toward market research, strategy formation, and coordinating activities. The study shows how GenAI reshapes B2B marketing processes and associated skill requirements, offering guidance for systematically embedding GenAI in industrial marketing.